2017
DOI: 10.1159/000479956
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Trans</i></b>-Fatty Acids and Cardiovascular Disease: Urgent Need for Legislation

Abstract: Hydrogenated oils containing trans-fatty acids (TFA) are used to produce margarine and various processed foods. TFA affect serum lipid levels, fatty acid metabolism, and endothelial function. High TFA intake is linked to increased all-cause mortality, coronary heart disease mortality, and cardiovascular disease (CVD) incidence. Denmark was the first country to introduce a law that limited TFA content in food; this action led to lower CVD mortality. So far 7 European countries have followed this practice, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…These partially hydrogenated trans-fatty acids that introduce at least one hydrogen bond in the trans configuration were originally developed to improve the quality and shelf life of baked goods and are used in margarine and commercial cooking. However, mounting evidence indicated that trans-fatty acids increased the risk of coronary heart disease mortality and cardiovascular disease incidence in a manner similar to saturated fatty acids [ 96 , 97 , 98 , 99 , 100 ]. As such, several European Countries introduced laws to limit the amount of trans-fatty acids in food [ 97 ].…”
Section: Dietary Cholesterol Saturated Fat Trans Fatty Acids Anmentioning
confidence: 99%
“…These partially hydrogenated trans-fatty acids that introduce at least one hydrogen bond in the trans configuration were originally developed to improve the quality and shelf life of baked goods and are used in margarine and commercial cooking. However, mounting evidence indicated that trans-fatty acids increased the risk of coronary heart disease mortality and cardiovascular disease incidence in a manner similar to saturated fatty acids [ 96 , 97 , 98 , 99 , 100 ]. As such, several European Countries introduced laws to limit the amount of trans-fatty acids in food [ 97 ].…”
Section: Dietary Cholesterol Saturated Fat Trans Fatty Acids Anmentioning
confidence: 99%
“…Furthermore, high TFA intake is generally considered as a risk factor for weight gain [9], although the evidence for the relationship between TFA intake and diabetes is inconsistent [10][11][12][13][14]. A recent meta-analysis confirmed that TFA intake is associated with all-cause mortality and coronary heart disease mortality [15].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been implemented to reduce the amounts of TFAs in processed foods. Indeed, it has been recommended that TFA limits should be established, because they represent the optimal solution when considering both CVD prevention and associated-cost savings in public healthcare [15]. To date, most European countries have established regulations that limits the TFA content in foods and many measures have been adopted to reduce the general population's intake of TFAs [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The Danish margarine industry had been willing to cooperate with Danish health professionals and had gradually eliminated industrially produced TFAs from their products even before the legislative ban was enacted in 2003 [ 14 ]. In Europe, a similar approach was later undertaken by Switzerland, Austria, Iceland, Hungary, Norway, and Latvia [ 15 ]. Another possible way to tackle the problem is to enact mandatory labelling of either TFAs or PHOs.…”
Section: Introductionmentioning
confidence: 99%